Policy Ideals vs. Classroom Realities: Teacher Readiness and Barriers in Kurikulum Merdeka - M Ragil Dwifani Azzura; Baiq Husnia Hamidayani; Siti Mukminatun (Al-Qalam Institue, 2025)
The nationwide implementation of Kurikulum Merdeka represents a significant paradigm shift toward student-centered learning in Indonesia; however, its operationalization has exposed deep structural challenges within the school ecosystem. This systematic literature review synthesizes empirical evidence from sixteen peer-reviewed articles published between 2023 and 2026 to evaluate teacher readiness, localized classroom friction, and institutional barriers across different educational strata. The findings demonstrate that initial teacher adaptation is severely constrained by low conceptual readiness regarding deep learning pedagogy, which is inadequately resolved by self-directed digital training tools such as the Platform Merdeka Mengajar (PMM). Furthermore, the review identifies a distinct structural divergence between educational levels: primary school teachers (SD) are primarily burdened by classroom management and tracking complexities driven by high student heterogeneity and a lack of verified diagnostic data, whereas secondary school instructors (SMA/SMK) are restricted by rigid content-pacing dilemmas, subjective grading metrics for differentiated products, and technological infrastructure deficits. Across all levels, the successful execution of pedagogical autonomy is systematically undermined by excessive administrative inflation, particularly the complex e-Rapor P5 application, which induces acute cognitive exhaustion and forces a dangerous shift from instructional quality to bureaucratic compliance. These insights imply that successful educational reform depends not on expanding standardized regulatory mandates, but on providing localized, tier-specific pedagogical coaching and structurally reducing institutional reporting burdens to restore instructional agency.